Microprocessor Based Firing Circuit for Static Slip Energy Recovery Controlled Slip Ring Induction Motor Drive - K Singh, B; B Naik, K (International Journal of Engineering and Technology, 2018)
Microprocessor based firing control scheme of static slip energy recovery (SER) controlled slip ring induction motor drive is described. In the scheme the microprocessor generates firing pulses and also decides the pair of thyristors of the controlled converter to be gated. It uses less number of hardware components. The oscillograms at different points of the firing circuit and at the output of the controlled converter are presented. These oscillograms resemble with the theoretical wave forms.